Hopeful Discourse: Elementary Children's Activist Responses to Modern-Day Slavery Grounded in Systems Thinking. (November 2019) - Curwen, Margaret Sauceda; Ardell, Amy; MacGillivray, Laurie
This qualitative case study examines how fifth graders and their teachers participated in critical literacy instruction grounded in systems thinking on the topic of slavery. Systems thinking seeks to discover relationships and patterns in diverse underlying systems; critical literacy examines everyday texts, focuses on social justice and change, and promotes transformative practices. Classroom observations, photographs, interviews, and student artifacts were collected and analyzed to provide insight into students' understandings of patterns of slavery from American colonial times to modern-day trafficking. Through a range of texts and different modalities, students sought to understand different group perspectives and ultimately took action to disrupt an unjust system. Three aspects of students' learning led them to an agentic role: (1) crossing boundaries across time and differences, (2) developing a holistic worldview, and (3) reimagining a different world and altering the existing discourse.